Analisis Profitabilitas, Solvabilitas dan Likuiditas terhadap Kinerja Perusahaan : (Emiten Property & Real Estate BEI Periode 2019-2023) - Jihan Salsabilah; Wastam Wahyu Hidayat; Gilbert Rely (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to find out whether profitability, solvency and liquidity influence company performance. The population in this research is property & real estate companies listed on the Indonesia Stock Exchange. The sampling technique used in this research is the purposive sampling method. The samples used in this research were property & real estate issuers, totaling 75 samples. This research uses secondary data obtained from the official website of the Indonesian Stock Exchange, namely www.idx.co. The analysis method used used the Statistical Package for Social Science (SPSS) software version 25. The research hypothesis was tested using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis tests and hypothesis testing. The results obtained in this research indicate that (1) profitability has a significant effect on company performance (2) solvency has a significant effect on company performance (3) liquidity has no effect on company performance.